Comparative Study of Dynamic Methods of Earthquake Resistant Structure - Siddharth Singh; Mohd Asraf; Chetan; Rajnish Kumar; Niharika Sharma (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Earthquake-resistant structural design necessitates a thorough understanding of seismic forces and their impact on buildings. This research paper investigates the effectiveness of different dynamic analysis methods, including response spectrum analysis and time history analysis, in predicting the dynamic response of structures under earthquake loads. The study compares these methods with static analysis, highlighting their strengths and limitations in capturing the complexities of seismic behaviour. The findings aim to provide insights for engineers to select the most appropriate analysis method for specific structural designs and seismic zones, ultimately contributing to safer and more resilient buildings.